Biophysics of the membrane interface. - Watts, A (1995)
It is clear that the interface is a highly complex region of the bilayer. In summary: (i) anionic lipids can interact in a stoichiometric way with charged protein residues; (ii) proteins are induced into 'molten globule' states on interaction with the membrane surface; (iii) local pH and hydration of the surface is not uniform and does not reflect the bulk properties; (iv) the contributions to the energetics of protein or peptide interaction are not well resolved and may not be readily measured; (v) as a result of electrostatic interactions between proteins and lipids, biomembranes may contain laterally separated domains that, at their interfaces, provide mismatched regions capable of permitting passage of components through the bilayer; (vi) the mode of insertion, folding and translocation may be determined directly by the surface properties of the biomembrane. Much still needs to be done to enable a complete description of the biophysics (mechanisms and energetics) of protein folding, insertion and translocation, and how this is affected by the bilayer surface, the initial site of interaction of such species. More experimental evidence, as well as theory to understand the results, is required before the measured thermodynamic parameters meet with descriptions of the various contributions for the process. Deuterium NMR is one direct and highly sensitive experimental approach to help in the understanding of such electrostatics at membrane interfaces.